THE DISTRIBUTION OF BENTHIC FORAMINIFERA IN DAMAR ISLAND AND JUKUNG ISLAND OF KEPULAUAN SERIBU - Natsir, Suhartati M. (Marine Research in Indonesia, 2010)
Kepulauan Seribu are an archipelago within Jakarta Bay built upon the pleistocene coral formation of the Sunda Shelf. The islands are characterised by a unique and high biodiversity such as coral reefs. Since coral reef degradation would lead to a decrease of human prosperity, the determination of the coral reef quality is of high importance. Foraminifers offer an early warning system for the coral reef condition, as exemplified by the FORAM Index, i.e. Foraminifera in Reef Assessment and Monitoring Index. This study compared the foraminiferal community structure and the FORAM Index of two islands, the Damar Besar and the Jukung Island. Both of the islands were dominated by symbiont-bearing foraminifera. However, the number of benthic foraminifers at Jukung Island was higher than that at Damar Besar Island, having 17 individuals per species on average. Jukung Island was a conducive site to reef growth, as indicated by a FORAM Index between 6,48 and 6.57, but Damar Besar Island was liable to environmental change. The symbiont-bearing foraminifers of both islands were members of the genera Amphistegina, Calcarina, Heterostegina, Marginophora, and Operculina.